Exploring potential polysaccharide utilization loci involved in the degradation of typical marine seaweed polysaccharides by Bacteroides thetaiotaomicron - Yu, Biao; Lu, Zheng; Zhong, Saiyi; Cheong, Kit-Leong (Frontiers in Microbiology, 2024)
Introduction Research on the mechanism of marine polysaccharide utilization by Bacteroides thetaiotaomicron has drawn substantial attention in recent years. Derived from marine algae, the marine algae polysaccharides could serve as prebiotics to facilitate intestinal microecological balance and alleviate colonic diseases. Bacteroides thetaiotaomicron, considered the most efficient degrader of polysaccharides, relates to its capacity to degrade an extensive spectrum of complex polysaccharides. Polysaccharide utilization loci (PULs), a specialized organization of a collection of genes-encoded enzymes engaged in the breakdown and utilization of polysaccharides, make it possible for Bacteroides thetaiotaomicron to metabolize various polysaccharides. However, there is still a paucity of comprehensive studies on the procedure of polysaccharide degradation by Bacteroides thetaiotaomicron. Methods In the current study, the degradation of four kinds of marine algae polysaccharides, including sodium alginate, fucoidan, laminarin, and Pyropia haitanensis polysaccharides, and the underlying mechanism by Bacteroides thetaiotaomicron G4 were investigated. Pure culture of Bacteroides thetaiotaomicron G4 in a substrate supplemented with these polysaccharides were performed. The change of OD600, total carbohydrate contents, and molecular weight during this fermentation were determined. Genomic sequencing and bioinformatic analysis were further performed to elucidate the mechanisms involved. Specifically, Gene Ontology (GO) annotation, Clusters of Orthologous Groups (COG) annotation, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment were utilized to identify potential target genes and pathways. Results Underlying target genes and pathways were recognized by employing bioinformatic analysis. Several PULs were found that are anticipated to participate in the breakdown of these four polysaccharides. These findings may help to understand the interactions between these marine seaweed polysaccharides and gut microorganisms. Discussion The elucidation of polysaccharide degradation mechanisms by Bacteroides thetaiotaomicron provides valuable insights into the utilization of marine polysaccharides as prebiotics and their potential impact on gut health. Further studies are warranted to explore the specific roles of individual PULs and their contributions to polysaccharide metabolism in the gut microbiota.